Hydraulic characterization of a highly anthropized coastal aquifer subject to tidal fluctuations - Fischer, P.; Jardani, A.; Krimissa, M.; Couegnas, C. (Hydrogeology journal, 2020)
The hydraulic characterization of a highly anthropized coastal aquifer in France is presented. The current industrial operations of the study site prevent the use of standard ‘active’ hydrogeological investigation methods (pumping, slug tests). However, the studied field is bordered on its north-western side by a channel directly connected to the sea, which allows for characterization of the hydraulic properties of the aquifer from its natural responses to the channel’s tidal signal. Piezometers (37) were monitored, from which oscillatory water-level responses (amplitude and phase-offset) to the tidal signal were extracted through linear regression and fast Fourier transform. A two-dimensional (2D) numerical model in the frequency domain was built to simulate the oscillations. The anthropic buried walls and barriers existing at the site are represented as 1D elements in a 2D model representing the properties of the aquifer. A deterministic inversion process optimizes the spatial distribution of aquifer properties and anthropic-structure properties in the model, in order to minimize the differences between the responses simulated with the model and those measured in the field. The results of the characterization on this complex study case (flows highly constrained by hydraulic barriers or buildings, and the impossibility to perform pumping tests) generate simulations able to reproduce the observed responses. The property and simulation maps generated make it possible to take into account the impact of the anthropic structures on the groundwater flows and to localize the parts of the hydraulic barriers where most exchanges between the channel and the aquifer occur.